Structure linkage, and sequence of the two genes encoding the delta and gamma subunits of the nicotinic acetylcholine receptor. - Nef, P (1984)
We have cloned and sequenced a fragment of the chicken genome approximately 9 kilobases in length that comprises the genes encoding the delta and gamma subunits of the nicotinic acetylcholine receptor. The two genes are homologous and have identical structures: both consist of 12 exons, some of which precisely correspond to predicted structural domains of the receptor subunits. The delta and gamma subunit genes are encoded by the same DNA strand and are very closely linked, there being only 740 base pairs between the last codon of delta and the initiator codon of gamma. Blot analysis demonstrates that the genes we describe are unique in the genome. Comparison of the predicted protein sequence for the corresponding subunits of chicken and of the elasmobranch Torpedo reveals a high degree of conservation in some but not all of the protein domains.